PENINGKATAN HASIL BELAJAR SISWA SEKOLAH DASAR DENGAN PENERAPAN MODEL STAD (STUDENT TEAM ACHIEVEMENT DIVISION) BERBANTUAN MEDIA PUZZLE - Hestining Ardiyanti; Erik Aditia Ismaya; Deka Setiawan (WASIS : Jurnal Ilmiah Pendidikan, 2021)
This study aims to describe the application of the STAD (Student Teams Achievement Division) learning model assisted by the puzzle media and to find an increase in student learning outcomes on the theme of 6 Heat and Its Transfer in My Country, grade V SD 7 Cendono.Classroom action research was carried out in class V SD 7 Cendono with 22 students as the research subject. This research lasted for two cycles, each cycle consisting of four stages, namely planning, implementing, observing, and reflecting. The independent variable is the STAD model. While the dependent variable is student learning outcomes. The research instruments were tests and documentation. The data analysis technique used is qualitative and quantitative data analysis techniques.The results showed that the application of the STAD learning model assisted by puzzle media could improve student learning outcomes. Student learning outcomes have increased from cycle I to cycle II, namely from the percentage of student completeness of 43% to 86%.